Book Reviews - Fielitz, Sonja; Hertel, Ralf; Budrewicz-Beratan, Aleksandra (Multicultural Shakespeare: Translation, Appropriation and Performance, 2011)
Wolfgang Weiss, Shakespeare in Bayern und auf Bairisch (Shakespeare in Bavaria and in Bavarian Regional Dialects), Passau: Verlag Karl Stutz, 2008, 1st ed. Pp. 201. ISBN: 978-3-88849-090-3. Manfred Pfister and Jürgen Gutsch (eds.), William Shakespeare’s Sonnets for the First Time Globally Reprinted: A Quatercentenary Anthology (with a DVD), Dozwil: Edition Signathur, 2009. Pp. 752. ISBN 978-3-908141-54-9. Re-playing Shakespeare in Asia, ed. Poonam Trivedi, Minami Ryuta, New York: Routledge 2010, 1st ed. Pp. 201. ISBN: 978-3-88849-090-3.